MENGEMBANGKAN KEMAMPUAN ANAK MELALUI PERMAINAN JUAL BELI UNTUK MENGEMBANGKAN SOSIAL DALAM BERINTERAKSI: MENGEMBANGKAN KEMAMPUAN ANAK MELALUI PERMAINAN JUAL BELI UNTUK MENGEMBANGKAN SOSIAL DALAM BERINTERAKSI - Sitanggang, Sonia Anjeli (JURNAL TALITAKUM: JURNAL PENDIDIKAN KRISTEN ANAK USIA DINI, 2022)
Abstract The purpose of this research is to find out how to develop children's abilities through buying and selling games for social skills in interaction. The results of the study are that through play children can develop their social skills, such as buying and selling games to build relationships with other children, adjust to peers, be able to understand their own behavior, and understand that every action has consequences. A balanced friendship relationship can be obtained if the child has self-confidence and can face various problems and find solutions. Social skills also make him easily accepted by other children because he is able to behave appropriately according to the expectations of his environment. Keywords: children's abilities, children's social, buying and selling games